Raising rivals' costs with environmental regulation: An intertemporal lobbying approach - Achim Körber (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper addresses the question why a lot of firms demand stricter environmental regulation. With non-identical producers within the same industry, lobbying for tighter environmental rules turns out to be an important strategy of raising rivals' costs. Furthermore, the paper explains when the potential target firms of stricter regulation in such an intra-industrial competition engage in counter-lobbying and when they remain silent.
Keywords: D72; K32; 330; Lobbying; Environmental Regulation; Umweltpolitik; Interessenpolitik; Duopol; Theorie